Lama Kebuntingan, Litter Size, dan Bobot Lahir Kambing Boerawa pada Pemeliharaan Perdesaan di Kecamatan Gisting Kabupaten Tanggamus - Adhianto, Kusuma; Ngadiyono, Nono; Kustantinah, Kustantinah; Budisatria, I Gede Suparta (Jurnal Penelitian Pertanian Terapan, 2012)
An experiment was conducted on 100 heads of Boerawa doe mated with male Boer. The parameters perceived were pregnancy periode, litter size, and birth weight. The study was undertaken at Boerawa goat development area Kecamatan Gisting Kabupaten Tanggamus. The data were analysed in SPSS versi 10. The results showed that pregnancy periode 159,31 + 4,37 days, litter size 1,62 + 0,65 heads, and birth weight 3.02 + 029 kg. Keywords: boerawa goat, pregnancy periode, litter size, birth weight